Wisdom is the Tree of Life - Pshenichny, Gennady (Bogoslovskie razmyšlenija, 2004)
The author of this work will endeavor to answer the question: What kind of mysterious trees were there in the Garden of Eden, the fruits of which either endowed humanity with eternal life or boded unavoidable death? Were there real trees in the middle of the garden, or is that merely figurative language used to convey important principles? If so, what are those principles? Why did God put such a strong accent on the tree of knowledge of good and evil, not permitting its fruit to be eaten under any circumstances? What was so alluring about the tree that the woman dared to disobey God and make an independent decision? Why did the consequences turn out to be irrevocable?The main focus of this article is to examine the principles behind God’s commandments allowing or prohibiting certain things, particularly what was behind the prohibition of eating fruit from the tree of the knowledge of good and evil. The author shows that even today, although God has closed off access to the tree of life in the Garden of Eden, people can still reach it and enjoy its fruit.